Astrocytes show increased levels of Ero1α in multiple sclerosis and its experimental autoimmune encephalomyelitis animal model. (21st September 2022) - Samtleben, Samira; Mina, Lucas; Yap, Megan C.; Branton, William G.; Yousuf, Muhammad Saad; Tenorio, Gustavo; Ballanyi, Klaus; Giuliani, Fabrizio; Kerr, Bradley J.; Power, Christopher; Simmen, Thomas
Abstract: Multiple sclerosis (MS) and its animal models are characterized by cellular inflammation within the central nervous system (CNS). The sources and consequences of this inflammation are currently not completely understood. Critical signs and mediators of CNS inflammation are reactive oxygen species (ROS) that promote inflammation. ROS originate from a variety of redox‐reactive enzymes, one class of which catalyses oxidative protein folding within the endoplasmic reticulum (ER). Here, the unfolded protein response and other signalling mechanisms maintain a balance between ROS producers such as ER oxidoreductin 1α (Ero1α) and antioxidants such as glutathione peroxidase 8 (GPx8). The role of ROS production within the ER has so far not been examined in the context of MS. In this manuscript, we examined how components of the ER redox network change upon MS and experimental autoimmune encephalomyelitis (EAE). We found that unlike GPx8, Ero1α increases within both MS and EAE astrocytes, in parallel with an imbalance of other oxidases such of GPx7, and that no change was observed within neurons. This imbalance of ER redox enzymes can reduce the lifespan of astrocytes, while neurons are not affected. Therefore, Ero1α induction makes astrocytes vulnerable to oxidative stress in the MS and EAE pathologies. Abstract : Upregulation of Ero1α within astrocytes causes mitochondrial ROS production and compromises the survival of this CNS cell type.